2021
DOI: 10.1016/j.isci.2021.103485
|View full text |Cite
|
Sign up to set email alerts
|

Terahertz exposure enhances neuronal synaptic transmission and oligodendrocyte differentiation in vitro

Abstract: Summary Terahertz (THz) frequency occupies a large portion of the electromagnetic spectrum that is between the infrared and microwave regions. Recent advances in THz application have stimulated interests regarding the biological effects within this frequency range. In the current study, we report that irradiation with a single-frequency THz laser on mice cortical neuron cultures increases excitatory synaptic transmission and neuronal firing activities. Microarray assay reveals gene expression dynami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
20
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(22 citation statements)
references
References 38 publications
(40 reference statements)
2
20
0
Order By: Relevance
“…The non-invasive procedure for imaging could capacitate for real-time in-vivo cancer detection and diagnosis, regular screening and patient monitoring [13]. This hypothesis is supported by several previously reported investigations whereby safe exposure levels have been achieved on the basal keratinocytes [15], on blood leukocytes [16] as well as mammalian cells of humans.…”
Section: Introductionsupporting
confidence: 55%
“…The non-invasive procedure for imaging could capacitate for real-time in-vivo cancer detection and diagnosis, regular screening and patient monitoring [13]. This hypothesis is supported by several previously reported investigations whereby safe exposure levels have been achieved on the basal keratinocytes [15], on blood leukocytes [16] as well as mammalian cells of humans.…”
Section: Introductionsupporting
confidence: 55%
“…However, only a few studies deal with the effects of THz radiation on the nervous system cells. For instance, Zhao et al, showed that THz radiation inhibited the proliferation of progenitors of mouse oligodendrocytes, but stimulated their differentiation in the mature forms with the following myelination of fibers [ 17 ]. An extensive study by Tan Sheng Zhi et al, showed that different neuron types, in both normal and tumor rodent cell lines, were distinct in their sensitivity to THz radiation [ 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Many studies verified that THz waves with different radiation frequencies, intensities, and time of exposure shed different effects on the functions (e.g., gene expression, synaptic transmission, and immune cytokines release) of the nervous system [30][31][32]. Also, the THz waves could cause structural changes of macromolecules (e.g., proteins, lipid membranes) in living cells [24,33].…”
Section: Introductionmentioning
confidence: 99%